Permanência e mudança da cultura machista: formação social de adolescentes - Parisoto, Dyeniffer Jessica Bezerra (2020)
This research analyzes the persistence and the change of macho culture and gender inequality in the social formation of adolescents from Cascavel-PR. The objective was to capture what has changed and what has remained of the macho culture among adolescents, based on a historical analysis of social and productive relations and the way relations between men and women are constituted, as well as social formation today. To this end, a literature review of the historical process was carried out, and in the first chapter the women’s history was analyzed, mainly in the categories of family relations, religion, work and feminist movements. In the second chapter, the history of women was observed, in the categories of women’s rights, education and social formation of adolescents. In order to better understand the current reality, besides perceiving the aspects of change and persistence of macho culture, as well as gender inequality, a field research was carried out with 145 adolescents from five public high schools (first and second years) in Cascavel - PR. For this purpose, a questionnaire was used as a data collection tool to capture their understanding on the subject. Based on the students’ answers, observing the geographic location of each school, the economic conditions of the neighborhood, family life, work, religious formation, school and contact with the media, we sought to point out which of these elements most contribute to the change or the persistence of the macho culture, as well as gender inequality. When quantifying and analyzing the responses, it was concluded that, although the debate is currently present in some sectors of society, there are still several aspects of macho culture and gender inequality in the social formation of adolescents. The adolescents’ answers show that it is difficult to understand which element contributes the most to maintain the macho culture and gender inequality, since the student tends to perceive the prevalence of this culture in the most distant environments, naturalizing it. Also, it was observed that the knowledge of the subject, even if in a relative way, is present among them, but in an abstract way, without relating to their practical experience. Finally, it is concluded that the change, the persistence of the macho culture and gender inequality are a synthesis of multiple determinations, therefore, there are several social elements, including structural ones, that contribute to this; however, school education, even if inserted in a larger context and permeated by contradictions, can contribute to instrumentalize the student to perceive these themes historically and critically